2016
DOI: 10.1371/journal.pgen.1006089
|View full text |Cite
|
Sign up to set email alerts
|

Remote Control of Intestinal Stem Cell Activity by Haemocytes in Drosophila

Abstract: The JAK/STAT pathway is a key signaling pathway in the regulation of development and immunity in metazoans. In contrast to the multiple combinatorial JAK/STAT pathways in mammals, only one canonical JAK/STAT pathway exists in Drosophila. It is activated by three secreted proteins of the Unpaired family (Upd): Upd1, Upd2 and Upd3. Although many studies have established a link between JAK/STAT activation and tissue damage, the mode of activation and the precise function of this pathway in the Drosophila systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
128
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(135 citation statements)
references
References 64 publications
(101 reference statements)
7
128
0
Order By: Relevance
“…Our results reinforce the possibility of an interaction between plasmatocyte function and gut homeostasis, and suggests that cytokines derived from hemocytes can trigger cell responses in the gut. These results are also in agreement with a recent publication showing that Upd3 from hemocytes can trigger intestinal stem cell proliferation [69]. Altogether, these results demonstrate that the interaction between hemocytes and the gut tissue are central to host health, and our data demonstrate that phagocytic defects can be associated with chronic gut inflammation and aberrant intestinal stem cell turn-over.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results reinforce the possibility of an interaction between plasmatocyte function and gut homeostasis, and suggests that cytokines derived from hemocytes can trigger cell responses in the gut. These results are also in agreement with a recent publication showing that Upd3 from hemocytes can trigger intestinal stem cell proliferation [69]. Altogether, these results demonstrate that the interaction between hemocytes and the gut tissue are central to host health, and our data demonstrate that phagocytic defects can be associated with chronic gut inflammation and aberrant intestinal stem cell turn-over.…”
Section: Discussionsupporting
confidence: 93%
“…Upd3, the Drosophila analogue of IL-6, can induce the JAK-STAT pathway, which regulates the systemic immune response and metabolic homeostasis in the fat body, as well as gut homeostasis [6,22,69,70]. Using RT-qPCR, we asked whether crq is required for upd3 expression upon Ecc15 infection.…”
Section: Resultsmentioning
confidence: 99%
“…Actin injection did not lead to the expression of the AMP genes Drs and Dpt , which were induced only upon experimental fungal or bacterial infection (Figure 2g, h). This indicates the absence of microbial contaminants in actin preparations and demonstrates that the response to actin differs from that to septic injury, in which induction of STAT targets is invariably accompanied by that of genes downstream of Toll or Imd (Agaisse et al, 2003; Chakrabarti et al, 2016; Brun et al, 2006). In this regard, TotM induction by actin was much greater than that elicited by injury (clean or septic) or by heat shock, which are classically regarded as inducers of the JAK-STAT signalling pathway (Agaisse et al, 2003; Chakrabarti et al, 2016) (Figure 2—figure supplement 1a and data not shown).
10.7554/eLife.19662.004Figure 2.G- and F-actin induce a unique sterile inflammatory response upon injection into Drosophila.
…”
Section: Resultsmentioning
confidence: 91%
“…Upd3 produced by haemocytes is essential to induce STAT responses in the fat body or in the intestine of flies subjected to septic injury or a high fat diet (Agaisse et al, 2003; Chakrabarti et al, 2016; Woodcock et al, 2015). To determine if haemocytes were similarly required for the fat body STAT response to actin, we genetically ablated them in adult flies using two haemocyte-specific ( croquemort or Hemolectin ) temperature-sensitive Gal80 ts -Gal4 drivers crossed to a UAS- rpr strain encoding Reaper, a protein that induces apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation